Cochlear implantation and mastoid obliteration in a patient with Alström Syndrome. (May 2020) - Hill, Robert G.; Dwyer, Kelley; Tirino, Jennifer; Whitley, Matthew
Abstract: Objectives: To describe the outcomes of cochlear implantation with mastoid obliteration in a patient with Alström Syndrome and chronic otorrhea. Methods: This is a single case discussion of a patient with Alström Syndrome and chronic otorrhea who underwent unilateral cochlear implantation and mastoid obliteration in January 2019. Subsequent contralateral procedure was performed 4 months later. Implantation was pursued due to the progressive sensorineural hearing-loss that is characteristic of Alström Syndrome. Serial Audiograms were obtained before and after procedure. Results: Following implantation, audiological reports improved to near normal thresholds from the previous 60–85 dB sloping hearing loss. The patient's language skills rapidly improved as well as the ability to express her personality. Mastoid obliteration effectively resolved the chronic otorrhea that further complicated this case. Conclusion: Cochlear implantation with mastoid obliteration was successful in improving hearing thresholds and resolving chronic otorrhea in a patient with Alström Syndrome.